Marcus Aurelius' rain miracle and the Marcomannic wars - Kovács, Péter, 1969- (Mnemosyne, Supplements, 2009)
The longest war of the Roman imperial period is the war Marcus Aurelius waged with the northern German and Sarmatian tribes. The best-known events of these wars were the lightning and rain miracles. Divine intervention saved the Roman troops who were surrounded by the Germans and suffering from a water shortage, by means of a lightning and rain miracle. Thunderbolts struck the enemy while the rain soothed the Romans' suffering. Several pagan and Christian versions of the miracle existed already in Antiquity. Péter Kovács examines these events and their sources in detail. The most important source is the Column of Marcus Aurelius in Rome. The scenes of the column depict the miracles as well and therefore it was studied separately. The author also sketches the history of the Marcomannic wars. He publishes all the sources of the miracles and examines the development of the legend from Antiquity to the 14th century.